Abundance and Habitat Diversity of Springtails (Insecta: Collembola) of Rajshahi City Corporation (Journal of Life and Earth Science, 2014)
DOI: http://dx.doi.org/10.3329/jles.v7i0.20132 J. Life Earth Sci., Vol. 7: 119-120, 2012